Kepentingan Toleransi Beragama dalam kalangan Pelajar Universiti: Kepentingan Tolerasi Beragama dalam kalangan Pelajar Universiti - Siti Marpuah,; Chan , Jun Wei; Anwar, Heru Saiful; Kholis, Nur; Akhyak,; Intan Farhana, (Journal of Social Transformation and Regional Development, 2021)
The reality of social life must be able to accommodate human differences and diversity. The choice of beliefs is one example of such diversity. The purpose of this research is to identify common practises carried out by university students regardless of religion or belief. This research will also look into whether religious tolerance is important. This is a quantitative study that uses a Google form to collect information related to the study's purpose. There are 120 first-year students who took Moral Studies Subject. The findings revealed that one of the manifestations of tolerance among students of all religions is to discuss together, donate regardless of religion, visit a sick friend, eat together, play sports together, and so on. The study's findings also revealed that 95 percent of respondents agreed that religious tolerance among university students of various religions is important.